Local Fashion Product Marketing Strategy in the Creative Digital Era - Herlambang, Fito; Azzahra, Ghefira Prisyilia; Purwanto, Eko; Fitria, Fitria (Universitas Pendidikan Nasional, 2025)
This study aims to examine the marketing strategies of local fashion products in the creative digital era. Using a qualitative literature review approach, the findings show that local fashion entrepreneurs in Indonesia increasingly adopt digital strategies such as social media utilization, influencer collaboration, SEO optimization, and the use of big data and AI. These strategies have proven effective in expanding market reach, building brand awareness, and fostering closer relationships with consumers, especially Gen Z, who value personalization and sustainability. This research highlights the importance of digital technology adaptation to build competitive advantage in an increasingly dynamic market environment.